2020
DOI: 10.1186/s12886-020-1322-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic capability of a linear discriminant function applied to a novel Spectralis OCT glaucoma-detection protocol

Abstract: Background: Bruch membrane opening-minimum rim width (BMO-MRW) assessment offers a new diagnostic use in glaucoma patients of the Glaucoma Module Premium Edition (GMPE) available for the Spectralis optical coherence tomography (OCT) system. The objective of our research was to evaluate the diagnostic benefits of examining BMO-MRW and peripapillary retinal nerve fibre layer (pRNFL) readings acquired with Spectralis OCT to distinguish between healthy and mild glaucoma patients, comparing those readings with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In contrast, Chauhan et al [30], Enders et al [31] and Malik et al [32] proved that BMO-MRW showed higher diagnostic ability compared to peripapillary RNFL. Bambo et al [33] did not find any differences between diagnostic ability of peripapillary RNFL and BMO-MRW in glaucoma. In the present study, we integrated both strategies to achieve a better model.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, Chauhan et al [30], Enders et al [31] and Malik et al [32] proved that BMO-MRW showed higher diagnostic ability compared to peripapillary RNFL. Bambo et al [33] did not find any differences between diagnostic ability of peripapillary RNFL and BMO-MRW in glaucoma. In the present study, we integrated both strategies to achieve a better model.…”
Section: Discussionmentioning
confidence: 87%
“…Studies by many authors have shown that changes in BMO-MRW occur earlier than changes in RNFL in patients with open-angle glaucoma [6,8,[10][11][12][13]. In other clinical studies, it has been found that the results of the assessment of the thickness of the layer of retinal nerve fibers with BMO-MRW and RNFL are comparable in patients with glaucoma [7,15,16] and in healthy subjects [17]. It has also been shown that BMO-MRW assesses the condition of the optic nerve better than ONH in patients with glaucoma and in healthy patients [11].…”
Section: Resultsmentioning
confidence: 99%
“…Measurements are made in radial scans of various meridians of the optic nerve disc. Clinical studies have shown that BMO-MRW is an objective and valuable diagnostic tool for assessing the degree of damage to the nerve fibers of the retina on the optic nerve disc [5][6][7][8][9][10][11][12][13][14][15][16][17]. Many studies have found that BMO-MRW is a more sensitive and specific parameter of the glaucomatous damage to the optic disc than the visual field, ONH and RNFL [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All OCT scans were acquired using the Glaucoma Module Premium Edition, which offers scan patterns and an updated reference database [ 17 ]. This module includes the patented Anatomic Positioning System.…”
Section: Methodsmentioning
confidence: 99%